2019
DOI: 10.1093/eurheartj/ehz435
|View full text |Cite
|
Sign up to set email alerts
|

Predicting cardiac electrical response to sodium-channel blockade and Brugada syndrome using polygenic risk scores

Abstract: Aims Sodium-channel blockers (SCBs) are associated with arrhythmia, but variability of cardiac electrical response remains unexplained. We sought to identify predictors of ajmaline-induced PR and QRS changes and Type I Brugada syndrome (BrS) electrocardiogram (ECG). Methods and results In 1368 patients that underwent ajmaline infusion for suspected BrS, we performed measurements of 26 721 ECGs, dose–response mixed modelling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 32 publications
1
39
0
4
Order By: Relevance
“…These results are in line with the previous reporting of better efficacy of statins in high-risk samples, for example, due to diabetes, hypertension, or high CRP concentrations [68]. A recent study demonstrated a potential role of PRS for electrocardiogram parameters in predicting the cardiac electrical response to sodium channel blockade [69].…”
Section: Prs In Treatment Choicesupporting
confidence: 91%
“…These results are in line with the previous reporting of better efficacy of statins in high-risk samples, for example, due to diabetes, hypertension, or high CRP concentrations [68]. A recent study demonstrated a potential role of PRS for electrocardiogram parameters in predicting the cardiac electrical response to sodium channel blockade [69].…”
Section: Prs In Treatment Choicesupporting
confidence: 91%
“…This demonstrates that predisposition to BrS can occur because of the presence of common genetic variants in sodium channel genes or the transcriptional regulator HEY2. Furthermore, association data from genome-wide association studies used to calculate weighted polygenic risk scores have been explored as predictive tools to anticipate the results of ajmaline challenges, with a study by Tadros and colleagues [78] describing the association between polygenic risk scores and the slowing of cardiac conduction with ajmaline. Thus, the role of common variants in disease susceptibility must be considered, and is much more important than previously recognized.…”
Section: Sodium Channel Mutationsmentioning
confidence: 99%
“…More recently, it has been shown that a BrS PRS could potentially be of clinical utility in the diagnostic strategy of BrS. 25 …”
Section: Identification Of Genetic Risk Variants In Rare Cardiac Disementioning
confidence: 99%